Aged mice ovaries harbor stem cells and germ cell nests but fail to form follicles - Diksha Sharma; Deepa Bhartiya (BMC, 2022)
Abstract Background We recently published evidence to suggest that two populations of stem cells including very small embryonic-like stem cells (VSELs) and ovarian stem cells (OSCs) in ovary surface epithelium (OSE) undergo proliferation/differentiation, germ cell nests (GCN) formation, meiosis and eventually differentiate into oocytes that assemble as primordial follicles on regular basis during estrus cycle. Despite presence of stem cells, follicles get exhausted with advancing age in mice and result in senescence equivalent to menopause in women. Stem cells in aged ovaries can differentiate into oocytes upon transplantation into young ovaries, however, it is still not well understood why follicles get depleted with advancing age despite the presence of stem cells. The aim of the present study was to study stem cells and GCN in aged ovaries. Methods OSE cells from aged mice (> 18 months equivalent to > 55 years old women) were enzymatically separated and used to study stem cells. Viable (7-AAD negative) VSELs in the size range of 2-6 µm with a surface phenotype of Lin−CD45−Sca-1+ were enumerated by flow cytometry. Immuno-fluorescence and RT-PCR analysis were done to study stem/progenitor cells (OCT-4, MVH, SCP3) and transcripts specific for VSELs (Oct-4A, Sox-2, Nanog), primordial germ cells (Stella), germ cells (Oct-4, Mvh), early meiosis (Mlh1, Scp1) and ring canals (Tex14). Results Putative VSELs and OSCs were detected as darkly stained, spherical cells with high nucleo-cytoplasmic ratio along with germ cells nests (GCN) in Hematoxylin & Eosin stained OSE cells smears. Germ cells in GCN with distinct cytoplasmic continuity expressed OCT-4, MVH and SCP3. Transcripts specific for stem cells, early meiosis and ring canals were detected by RT-PCR studies. Conclusion Rather than resulting as a consequence of accelerated loss of primordial follicle and their subsequent depletion, ovarian senescence/menopause occurs as a result of stem cells dysfunction. VSELs and OSCs exist along with increased numbers of GCNs arrested in pre-meiotic or early meiotic stage in aged ovaries and primordial follicle assembly is blocked possibly due to age-related changes in their microenvironment.